2016
DOI: 10.1371/journal.pone.0166883
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed Proteins in Hypervirulent Clade 8 and Clade 6 Strains of Escherichia coli O157:H7 Compared to E. coli O157:H7 EDL933 Clade 3 Strain

Abstract: Escherichia coli O157:H7 is responsible for severe diarrhea and hemolytic uremic syndrome (HUS), and predominantly affects children under 5 years. The major virulence traits are Shiga toxins, necessary to develop HUS and the Type III Secretion System (T3SS) through which bacteria translocate effector proteins directly into the host cell. By SNPs typing, E. coli O157:H7 was separated into nine different clades. Clade 8 and clade 6 strains were more frequently associated with severe disease and HUS. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
1
14
0
1
Order By: Relevance
“…A study in 2008 identified a subtype of E. coli O157:H7, termed clade 8, associated with increased risk of HUS [10]. Although numerous studies have investigated virulence factor expression that may be responsible for this association [1114], studies confirming the association have been limited, suggesting an effect of varying strength and specificity [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…A study in 2008 identified a subtype of E. coli O157:H7, termed clade 8, associated with increased risk of HUS [10]. Although numerous studies have investigated virulence factor expression that may be responsible for this association [1114], studies confirming the association have been limited, suggesting an effect of varying strength and specificity [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…The EHEC O157:H7 strains Rafaela II (clade 8) and 7.1 Anguil (clade 6) isolated from cattle in Argentina and EDL933 (clade 3) strain recovered from a patient in USA were routinely maintained in Luria-Bertani broth (LB, Difco Laboratories, USA) or in LB 1.5% bacteriological agar plates, at 37°C. For the proteomic studies, bacterial strains were cultured as previously described by Amigo et al (7). Overnight cultures of the different EHEC O157:H7 strains growth in LB were inoculated (1:50) in Dulbecco’s modified Eagle’s medium (DMEM)-F12 nutrient until reach the mid-exponential growth phase (OD 600nm =0.6) under a 5% CO 2 atmosphere at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…After bacterial growth, protein extractions were performed according to Amigo et al (7). Three biological replicates of each culture were centrifuged at 5000 × g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversed-Phase Fractionation. The mixed TMT labelled peptides were desalted with Sep-Pak SPE cartridges (Waters) for subsequent hpRP separation in a Dionex Ulti-Mate 3000 model as described previously [10]. Finally, 48 collected fractions were merged into 12 mixtures (Supplementary figure 1).…”
Section: High Phmentioning
confidence: 99%